EVALUATION OF THE PHYSICAL FITNESS AMONG THE STUDENTS OF THE ALI HASYIMI PUBLIC HIGH SCHOOL IN THE DISTRICT OF ACEH BESAR - Zulfikar, Zulfikar; Rahayu, Tandiyo; Sulaiman, Sulaiman (The Journal of Educational Development, 2017)
Quality education is the basic thing that must be addressed by the Indonesian government. Among the causes of the slow pace of education progress in Indonesia are geographical problems and the lack of a permanent curriculum to be conducted continuously throughout Indonesia. The district of Aceh Besar has assigned some high schools to become model schools. The model schools have the best-selected teachers as a result of a competition in Aceh Besar and each school has two physical education teachers. In order to know the high or low level of the students’ physical fitness, it needs proper and accurate assessment. In order to know the exact level of the students’ physical fitness, physical education teachers require appropriate measuring instruments. The standard measuring instrument already used by physical education teachers today is the Indonesia Physical Fitness Test. The purpose of this study is to describe the level of physical fitness among the students of the Ali Hasyimi Public High School in the District of Aceh Besar in the 2014/2015 school year. To obtain data in this study, the researcher used a descriptive type of research that seeks to describe, record, and interpret the conditions that occur currently in relation to the level of physical fitness. The approach used to obtain the research data was a test and assessment. The samples in this study were all high school students of the Ali Hasyimi Public High School in the District of Aceh Besar drawn with a total sampling technique. The data were then analyzed using a simple formula including average and percentage. The average value of physical fitness possessed by the male and female students of the state senior high schools in Aceh Besar district in the 2014/2015 school year was measured using the Indonesia Physical Fitness Test and had been adjusted to the norms of the test, as well as confirmed in the table. The category was average. The detailed percentages are as follows. 1). A total of 23 male students (40.35%) were in the average category, 2). A total of 34 male learners (59%) were in the poor category, 3). No learner who was in the category of less than adequate, good and excellent.